2016
DOI: 10.1021/acs.biochem.6b01025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protein Tyrosine Phosphatase 1B Inhibition by Chlorogenic Acid and Cichoric Acid

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a known regulator of the insulin and leptin signaling pathways and is an active target for the design of inhibitors for the treatment of type II diabetes and obesity. Recently, cichoric acid (CHA) and chlorogenic acid (CGA) were predicted by docking methods to be allosteric inhibitors that bind distal to the active site. However, using a combination of steady-state inhibition kinetics, solution nuclear magnetic resonance experiments, and molecular dynamics simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…This disperse set of residues might suggest that AA binds to multiple sites, but its distribution (five residues appear in flexible loops, and three are buried in regions distal to known binding sites) suggests that changes in protein conformation and/or dynamics are a more likely cause. This effect is consistent with the results of previous NMR analyses, which indicate that the binding of inhibitors to the active site or C-terminal allosteric site (Figure C) can trigger CSPs at both sites and within intermediary regions of the protein; PTP1B thus appears to be quite flexible. , The absence of an obvious binding site for AA (i.e., a clustered set of residues with large CSPs) is surprising but could result from multiple bound conformations; this mode of interaction is compatible with the weak inhibitory effect of AA and with the generally low CSPs (i.e., <0.1 ppm) detected in our experiments . Our NMR results, taken together, indicate that AA modulates the conformation and/or dynamics of PTP1B by adjusting a broadly distributed set of intraprotein interactions that extends beyond its binding site.…”
Section: Resultssupporting
confidence: 90%
“…This disperse set of residues might suggest that AA binds to multiple sites, but its distribution (five residues appear in flexible loops, and three are buried in regions distal to known binding sites) suggests that changes in protein conformation and/or dynamics are a more likely cause. This effect is consistent with the results of previous NMR analyses, which indicate that the binding of inhibitors to the active site or C-terminal allosteric site (Figure C) can trigger CSPs at both sites and within intermediary regions of the protein; PTP1B thus appears to be quite flexible. , The absence of an obvious binding site for AA (i.e., a clustered set of residues with large CSPs) is surprising but could result from multiple bound conformations; this mode of interaction is compatible with the weak inhibitory effect of AA and with the generally low CSPs (i.e., <0.1 ppm) detected in our experiments . Our NMR results, taken together, indicate that AA modulates the conformation and/or dynamics of PTP1B by adjusting a broadly distributed set of intraprotein interactions that extends beyond its binding site.…”
Section: Resultssupporting
confidence: 90%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%
“…Another enzyme, protein tyrosine phosphatase 1B (PTP1B) negatively regulates the insulin signaling pathway by inhibiting the activity of insulin receptor kinase (56). Two studies with molecular docking showed the molecular interactions between the allosteric site of PTP1B and chicoric acid, which suggests chicoric acid might inhibit PTP1B and further activate the insulin signaling pathway (57,58).…”
Section: Chicoric Acid and Glucose Metabolismmentioning
confidence: 99%